Hydrogels for the treatment of radiation-induced skin and mucosa damages: An up-to-date overview - Su, Yidan; Cui, Hengqing; Yang, Chao; Li, Lu; Xu, Fei; Gao, Jie; Zhang, Wenjun (Frontiers in Materials, 2022)
Radiation-induced damages are difficult to heal than normal wounds. This is because radiation therapy could lead to an imbalanced inflammatory response, oxidative stress response, lack of angiogenesis, and a high risk of bacterial infection, which are considered to be the greatest challenges in radiation-induced damages treatment. Hydrogels are semi-occlusive and are composed of complex hydrophilic polymers with a higher water content. Due to their excellent mechanical and biochemical property (such as adhesiveness, antibacterial, and antioxidant abilities), hydrogels represent a promising strategy that has achieved potent therapeutic efficacy in the treatment of radiation-induced skin and mucosa damages. This review systematically and comprehensively summarizes the recent progress of various types of hydrogels such as natural biopolymer, synthetic polymer, composite hydrogels and commodity dressings for the treatment of radiation-induced skin and mucosa damages.